Horizons of Historical Narratology - Olga A. Grimova (Studia Litterarum)
The article is devoted to the analysis of two pieces of research that develop the idea of diachronic consideration of narratological categories in application to the Russian literary process — the monograph by V.I. Tupa “Horizons of Historical Narratology” and the collective work “Thesaurus of Historical Narratology (Based on Russian Literature): An Experimental Dictionary.” The purpose of the article is to present the worldview and axiological principles, conceptual and methodological innovations of the emerging scientific school, and to define its role in the space of modern humanities. A semantic approach to storytelling, inspired by the work of P. Riker, is a priority for scholars developing a project of historical narratology. The narrative appears not as a sphere of constructive techniques but as a space of interaction of strategies formed by culture and tactics embodying the author’s initiative. The article concludes with the undoubted heuristic and methodological perspective of the historical narratological project and its conceptual and ideological relevance.